Green synthesis of nickel oxide nanoparticles using Acacia nilotica leaf extracts and investigation of their electrochemical and biological properties. Issue 1 (31st December 2023) - Hussain, Shabbir; Ali Muazzam, Muazzam; Ahmed, Mahmood; Ahmad, Muhammad; Mustafa, Zeeshan; Murtaza, Shahzad; Ali, Jigar; Ibrar, Muhammad; Shahid, Muhammad; Imran, Muhammad
Abstract : Green synthesis of nanoparticles (NPs) has attracted the researcher's attention due to its rapid, cost-effective, sustainable and eco-friendly nature. Current studies were carried out to perform and investigate the green synthesis of NiO NPs with aqueous (NiO(aqueous)) and ethanolic extracts (NiO(ethanolic)) of Acacia nilotica leaves, respectively. The NPs were characterized by spectroscopic, microscopic and thermometric techniques including FTIR, Raman, XRD, SEM, TGA and DSC. The electrochemical properties, antibacterial potential and haemolytic activities of the synthesized NPs were also examined. XRD patterns revealed the face-centred cubic structures of NiO NPs and a high degree of crystallinity. The average crystallite size of NiO(aqueous) NPs was significantly smaller (16 nm) than that of NiO(ethanolic) NPs (28 nm). SEM images show that NiO NPs are spherical. The synthesized NiO NPs demonstrate good electrochemical stability at an operating potential of −0.5-0.5 V. The inhibition effect of NiO NPs(ethanol) against B. subtilis, was comparable to the ciprofloxacin.